Analisis Pengembangan Desa Wisata Berbasis Digital Dalam Meningkatkan Perekonomian Masyarakat Deli Serdang Dalam Kajian Ekonomi Islam - Devi Nadya Hasibuan; Sri Ramadhani; Rahmat Daim Harahap (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Deli Serdang is a district that has natural beauty and cultural diversity that can attract tourists, one of which is the existence of a tourist village. A digital-based tourism village is a village that is managed and developed by utilizing technological developments. This research is qualitative research using interview and observation methods. This study aims to determine the